Nitrogen balance in a goat farm producing milk in the county of Barva, Costa Rica - Jiménez, José P. (2014)
The objective of this study was to quantify the use of N in a goat milk producer farm located in the province of Heredia. Data such as feed purchases, milk sales, purchase and removal of animals was compiled and analyzed between January and December 2012. In order to evaluate the use of N, three indicators that allowed analyzing farm efficiency were used. Total number of animals was 102. Annual milk production was 22.417,5 kg. The farm imported 729,8 kg of nitrogen, of which 71% came from feed and only 29% from fertilizers. Farm exported 113,3 kg of nitrogen, of which 85,3% was exported as milk and only 14,7% as animals. The farm imported 38,7 g of N per kg of milk produced. In general, N balance was positive for all farms, indicating that more N entered the farm that came out in the form of product, showing that up to 84,5% of all imported N remained in the farms. Our results suggests that strategies to reduce N excretion should be developed, including improvements in the diet, since the largest N input is through imported feed.